A high functional cure rate was induced by pegylated interferon alpha-2b treatment in postpartum hepatitis B e antigen-negative women with chronic hepatitis B virus infection: an exploratory study - Zhong, Wenting; Yan, Lanzhi; Zhu, Yage; Shi, Lei; He, Yingli; Chen, Tianyan; Zheng, Jie (Frontiers in Cellular and Infection Microbiology, 2024)
Background and aimsLimited data have been reported on achieving functional cure using pegylated interferon (Peg-IFN) alpha-2b treatment for postpartum hepatitis B e antigen (HBeAg)-negative women with chronic hepatitis B virus (HBV) infection. This study was to assess the effectiveness and safety of Peg-IFN alpha-2b in HBV postpartum women without HBeAg and identify factors linked to the functional cure.MethodsA total of 150 HBeAg-negative postpartum women were retrospectively recruited.47 patients received Peg-IFN alpha-2b [Peg-IFN(+) group] and 103 patients did not [Peg-IFN(-) group]. Propensity score matching (PSM) was used to adjust the baseline imbalance between the two groups. The patients were followed for at least 48 weeks. The primary endpoints were hepatitis B surface antigen(HBsAg) loss and HBsAg seroconversion at 48 weeks. Logistic regression analysis was used to assess factors associated with HBsAg loss at 48 weeks.ResultsAt week 48,the HBsAg loss and seroconversion rate in Peg-IFN(+) group were 51.06%(24/47) and 40.43%(19/47), respectively. Even after PSM, Peg-IFN(+) group still showed higher HBsAg loss rate (50.00% vs 7.14%,p<0.001) and higher HBsAg seroconversion rate (38.10% vs 2.38%,p<0.001). Baseline HBsAg levels (Odds Ratio [OR]: 0.051, 95% Confidence Interval [CI]: 0.003-0.273, P=0.010), HBsAg at week 24 (OR:0.214, 95%CI:0.033-0.616, P=0.022), HBsAg decline at week 24 (OR:4.682, 95%CI: 1.624-30.198, P=0.022) and postpartum flare (OR:21.181, 95%CI:1.872-633.801, P=0.030) were significantly associated with HBsAg loss at week 48 after Peg-IFN alpha-2b therapy. Furthermore, the receiver operating characteristic curve (ROC) showed that the use of baseline HBsAg<182 IU/mL, HBsAg at week24 < 4 IU/mL and HBsAg decline at week24>12IU/mL were good predictors of HBsAg loss. No serious adverse events were reported.ConclusionPeg-IFN alpha-2b treatment could achieve a high rate of HBsAg loss and seroconversion in HBeAg-negative postpartum women with reliable safety, particularly for patients experience postpartum flare and have low baseline HBsAg levels.